The Perception of Teachers and Students on the Development of Code Learning Model in Learning English Productive Skills - Zelvia Liska Afriani; Muhammad Taufiqurrahman; Ixsir Eliya (English Education Study Program Faculty of Teacher Training and Education, 2022)
The present research aims to examine teachers and students perception in developing Code Learning Model in learning English productive skills, speaking and writing. The researchers utilized a descriptive study conducted in five universities in Bengkulu. Two hundred and sixteen students were randomly selected from sixth semester students studying in the English department participated in the study. Also, seventeen teachers were included in giving their comments on the questionnaire. The results of this study reveal that according to the perceptions of teachers and students, a coding learning model is essential and can be alternative learning in the era of the industrial revolution 4.0 that puts forward the use of technology. The application of this model can train students' 21st-century competencies and computational thinking because they align with today's developments. It can also motivate students to learn productive English skills to be more exciting and accessible.